Importance of incorporating intraoperative neuromonitoring of the external branch of the superior laryngeal nerve in thyroidectomy: A review and meta‐analysis study. Issue 6 (1st February 2019) - Naytah, Mai; Ibrahim, Iman; da Silva, Sabrina
Abstract: Background: Voice changes are frequently reported after thyroidectomy due to injury to the external branch of the superior laryngeal nerve (EBSLN) and paralysis of the cricothyroid muscle, The objective is to evaluate the advantage of intraoperative neuromonitoring (IONM) in identifying EBSLN during thyroid surgery. Methods: Data sources were MEDLINE, PubMed, Web of Science, and Cochrane Library from January 1, 1995, through July 1, 2018. Published studies of adult patients who had thyroid surgery and an attempt to identify EBSLN done by conventional methods and/or IONM were selected. Results: Seven studies met all inclusion criteria. Patients who had IONM during thyroid surgery had a significantly increased number of identified EBSLN at risk, compared to the control group. Conclusion: The use of IONM during open thyroid surgery increases EBSLN identification/visualization, and hence it may decrease the incidence of post‐thyroidectomy voice disorders.